Study on Motorcycle Speed Characteristics at Various Speed Limit Zones on Federal Route FT050 - Adnan, Ainatul Adni Farisha; Omar, Noorliyana (Recent Trends in Civil Engineering and Built Environment, 2021)
Batu Pahat district recorded a very high increase in accident rates from time to time. KM1-KM32 Jalan Persekutuan FT050 is a road in Batu Pahat District that often causes road accidents that result in death. Among the factors contributing to the accident was the human factor which contributed 99.2%, followed by environmental factors of 5.4%, and vehicles of 0.5%. This study was conducted to determine the level of compliance of motorcyclists at hot spot location at Jalan Persekutuan FT050. This study uses the GlobalSat DG-200 GPS measurement tool for data collection and uses Microsoft Excel software to analyze data by 36 trips from Batu Pahat to Ayer Hitam and 29 trips from Ayer Hitam to Batu Pahat. The research findings show that riders do not comply with the rules of the road that is by violating the set speed limits of 30 km/h and 60 km/h.